Eye Movement Modeling Examples guide viewer eye movements but do not improve learning. (June 2022) - Wright, Anna M.; Salas, Jorge A.; Carter, Kelly E.; Levin, Daniel T.
Abstract: Recent research has tested whether Eye Movement Modeling Examples (EMMEs) can effectively cue attention and improve learning. However, the effects of EMMEs are variable, and the degree to which viewers follow these cues remains unclear. In the current paper, we compared screen-captured instructional videos that included an EMME in the form of a transparent circular overlay depicting the instructor's gaze location with identical videos that lacked this cue. We observed that EMMEs drove viewer saccades to cued locations and resulted in shorter distances between viewer gaze and the EMME, but learning performance and video preference were unaffected by the presence of an EMME. We argue that EMMEs can effectively guide attention, but the range of circumstances under which they improve learning may be limited. Highlights: Eye Movement Modeling Examples did not improve learning from screen-captured videos. EMMEs increased perceived workload and decreased video preference. Two novel measures verified that viewers do follow EMMEs.